Combining functional exercises with exercise training in COPD: a randomized controlled trial - Francisco de Lima, Fabiano [UNESP]; Marçal Camillo, Carlos Augusto; Grigoletto, Isis [UNESP]; Uzeloto, Juliana [UNESP]; Marques Vanderlei, Franciele [UNESP]; Ramos, Dionei [UNESP]; Burtin, Chris; Cipulo Ramos, Ercy Mara [UNESP] (Taylor & Francis, 2022)
Introduction: Increasing physical activity in daily life (PADL) in chronic obstructive pulmonary disease (COPD), mainly in short-term training programs, is still a challenge. The combination of functional exercises with aerobic and resistance training may be a strategy to improve PADL and limitations in activities of daily living (ADL) in COPD. Objective: To evaluated the short- and medium-term effects of the combination of functional exercises with aerobic and resistance training. Methods: Seventy-six patients were randomized into (1) functional training group who performed resistance and aerobic and functional exercises; (2) conventional training group (CTG) who performed resistance and aerobic exercise; or (3) usual care group who performed respiratory physiotherapy. Patients were evaluated for PADL (activity monitor), ADL limitations (London Chest Activity of Daily Living scale [LCADL]), functional exercise capacity (6-minute walk test [6MWT]), and peripheral muscle strength before and after eight weeks. Medium-term effects were evaluated 12 weeks after the training. Results: There were no changes or differences between groups in PADL and in 6MWT post-intervention and 12 weeks post-training. Only CTG showed a reduction in the total score on LCADL scale after the intervention and increase at follow-up (score: 20 ± 8; 17 ± 6; 19 ± 8, pre-intervention, post-intervention, and 12 weeks post-training, respectively, p = 0.001), without differences between groups (p = 0.375). There were increases in the muscle strength of knee flexors (p = 0.016) and extensors (p < 0.001) after the intervention only in CTG. Conclusions: Combined aerobic and resistance training with functional exercises failed to improve PADL and ADL limitations in COPD. Eight weeks of conventional training improved ADL. This, however, was not superior to the results from the other groups and was not sustained at medium-term 12 weeks post-training.
Keywords: Chronic obstructive pulmonary disease; exercise training; physical activity